Steam experimental researches of metal polymer friction taking into account triboelectric processes. - Криштопа, С.І.; Криштопа, Л.І.; Прунько, І.Б.; Мельник, В.М.; Гнип, М.М. (Problems of Tribology, 2016)
Specific of metal polymer materials consists on their work in tribopairs is accompanied by the processes of tribo-electrization and also destructions with formation of different phases which going back into initial stance have other power levels of superficial and subsuperficial layers. Active products being get thus chemically co-operate with the rough spots of contacts of microledges of metallic element. It is known that friction pair «polymer-metal» has a different energy loading in friction co-operation of tribopairs. Superficial and subsuperficial layers of polymeric protective strap are the stores of charges volume and properties of which change depending on their energy loading. The last one makes huge affects on mechanical, electric and thermal the fields. In addition, microledges of contacts of metallic element participate actively in forming of tri-boelectrochain. During friction process there is the local contact of microledges here during the contact the electrons and ions move from one body to second one. The contact difference of potentials of two bodies arises up as a result of transition of electrons through the contact from a body with less energy of electron output to the body with greater energy. Thus electrons and ions can pass both from a dielectric to the metal and vice versa charging surface of dielectric both positively and nega-tively in relation to the surface of metal. Coming foregoing from there are actual experimental researches of wearing proper-ties of metal polymer pairs of friction of tribosystem. Keywords: metal polymer friction pairs, drum-block brake, tribosystem, triboelectricity.